Anne of ingleside eaudiobook - Montgomery, L. M. (Anne of Green Gables, 2017)
The mother of five, Anne never has a dull moment in her home, and, now with a new baby on the way and insufferable Aunt Mary Maria visiting-and wearing out her welcome-her life is full to bursting. Still, Mrs. Doctor can't think of any place she'd rather be than her own beloved Ingleside-that is, until the day she begins to worry that her adored Gilbert doesn't love her anymore. But how could that be? She may be a little older, but she's still the same irrepressible, irreplaceable redhead-the wonderful Anne of Green Gables, all grown up and ready to make her cherished husband fall in love with her all over again!